HISTORITAS EVOLUSI SISTEM KEWARISAN ISLAM : (Kajian Tematik ayat-ayat Waris Fase Pra Islam dan Fase Madinah) - Ubaidillah, M. Burhanuddin; Fatimatuz Zahro’, Nur (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
The study of Islamic inheritance systems is a serious topic of inquiry among Islamic thinkers because it includes Allah's ordinances. Various interpretations of inheritance verses have developed and given rise to diverse methods of Islamic inheritance distribution. For example, the Sunni inheritance system is a common model among methods of inheritance distribution, characterized by a patrilineal pattern. Hazairin interprets inheritance verses through a contextual approach to the society in Indonesia, resulting in a parental or bilateral inheritance system. Unlike Syahrur, he believes that there are maximum and minimum limits in the concept of Islamic law set by Allah, making Islamic law both certain and flexible for interpretation within those limits. Syahrur approaches the interpretation of inheritance verses using a mathematical approach, resulting in the theory of limits (hudud). This article will examine the historical evolution of Islamic inheritance systems, focusing on the thematic phases of Pre-Islam and the Medinan period, starting with inheritance verses in the Quran, the Arab Tribal and Medinah phases, definitions of inheritance, the historical evolution of Islamic inheritance systems in the Pre-Islam and Medinah phases, which include three inheritance systems in the Pre-Islam phase through lineage and kinship, adoption (tabanni), and covenantal bonds, and the Islamic inheritance system in the Medinah phase.